Diagnostic significance of Philadelphia chromosome BCR-ABL fusion gene detected by GTG-banding and reverse-transcription polymerase chain reaction (RT-PCR) in Filipino patients with chronic myelogenous leukemia (CML) - Amarillo, Ferdinand F. (Animo Repository, 2003)
Introduction. Chronic myelogenous leukemia (CML) is a good clinicla model for showing the capabilities and limitations of cytogenetic and molecular tools in the detection and progress surveillance of the disease. Its hallmark at the level of the chromosomes is the reciprocal translocation of chromosomes 9 and 22 producing the so-called Philadelphia chromosome (shortened chromosome 22). At the molecular level it is characterized by the presence of a BCR-ABL fusion gene believed to be responsible for the malignant transformation of cells. Objectives. 1)To detect the Ph chromosome using the routine cytogenetic GTG banding; 2) To detect BCR-ABL fusion gene by nested RT-PCR; 3) To compare the detection rate of cytogenetic tool with RT-PCR int he diagnosis of CML and disease progression Methods. Peripheral blood samples or bone marrow aspirates were collected from 29 Filipinos with clinically diagnosed CML. The samples were processed both for cell culture and RNA extraction. Chromosomes harvested from primary cultures were differentially stained and analyzed. Qualitative RT-PCR detection of BCR-ABL gene fusion was doe using 2 primers specific for detecting b2a2 and b2a3 fusion. Results. Cytogenetic analyses revealed the presence of the Philadelphia chromosome in 17 (58.62%) patients. Using the RT-PCR method, amplified BCR-ABLL transcripts were detected in 28 (96.55%) patients. Of these, 15 patients have the b3a2 fusion gene, 7 are the b2a2 fusion type and 6 have both the b3a2 and b2a2 fusion. Conclusion. Data obtained from this study show that RT-PCR technique has comparatively higher detection rate than cytogenetic analysis. Thus, the use of RT-PCR proved more sensitive in detecting CML.